Newborn Hearing Screening and Intervention in Children with Unilateral Hearing Impairment: Clinical Practices in Three Nordic Countries - Nina Jakhelln Laugen (MDPI AG, 2021)
Studies have limitedly considered children with early-identified unilateral hearing impairment (UHI), and clinical practices regarding screening, diagnostics and habilitation in this group are rarely documented. In this study, routines for newborns with UHI from screening to diagnostics and habilitation were explored in Norway, Sweden and Finland. An online survey was sent to hospitals responsible for the hearing diagnostics of children requesting information about their practices regarding congenital UHI. Responses covered 95% of the children born in the three included countries. The results revealed large variations in ways of organising healthcare and in clinical decisions regarding hearing screening, diagnostics and habilitation of children with congenital UHI. Finally, implications for policy making and research are also discussed.